Duodenocolic Fistula: A Rare Complication of Gastrointestinal Tuberculosis - Iñaki L. Garcia, Julian; V. Romero, Ronald (Journal of Clinical Case Reports and Images, 2022)
Introduction Benign duodenocolic fistula (DCF), also known as a non-malignant fistula between the duodenum and colon, with or without cecum-involvement, is an unusual complication of different gastrointestinal (GI) diseases 12. Case This is a case of a 28-year-old Filipino female who presented with periumbilical pain for five months, with associated anorexia, fever, and weight loss. Biopsy showed chronic granulomatous inflammation with caseation necrosis and Langhan’s type giant cells consistent with tuberculous etiology (Figure 6 and Figure 7). Category I Anti-TB treatment for six months was started and the service planned to repeat both colonoscopy and CT-scan after the initial round of anti-TB treatment. Conclusion Benign duodenocolic fistula in the form of extrapulmonary TB is a rare GI finding that is triggered by inflammatory processes. Proper management in this case was to treat the underlying TB infection which is endemic in the Philippines.
Keywords: Benign Duodenocolic Fistula; Tuberculosis; Gastrointestinal Tuberculosis